2007
DOI: 10.1002/eji.200636915
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocyte induction of rapid effector function in antigen‐specific memory CD4+ and CD8+ T cells

Abstract: The ability of human keratinocytes to present antigen to T cells is controversial and, indeed, it has been suggested that keratinocytes may promote T cell hyporesponsiveness. Furthermore, it is unclear whether keratinocytes can process antigen prior to MHC class I and class II presentation. We tested the ability of keratinocytes to induce functional responses in epitope-specific CD4 + and CD8 + memory T cells using peptides, protein and recombinant expression vectors as sources of antigen. Keratinocytes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 37 publications
(37 reference statements)
6
90
1
1
Order By: Relevance
“…The immune response induced by calcipotriol plus 5-FU against actinic keratoses resembled skin allograft rejection (28), accompanied by HLA class II and MICB expression on the malignant keratinocytes. HLA class II expression by lesional keratinocytes signifies their role as antigen-presenting cells in the context of the adaptive immune response induced by calcipotriol plus 5-FU treatment (29) and provides evidence that CD4 + T cells infiltrating the actinic keratoses can directly target these malignant keratinocytes. Notably, NKG2D ligand induction on keratinocytes by calcipotriol plus 5-FU treatment has been shown to synergize with TSLP to suppress skin cancer development (3, 30).…”
Section: Discussionmentioning
confidence: 99%
“…The immune response induced by calcipotriol plus 5-FU against actinic keratoses resembled skin allograft rejection (28), accompanied by HLA class II and MICB expression on the malignant keratinocytes. HLA class II expression by lesional keratinocytes signifies their role as antigen-presenting cells in the context of the adaptive immune response induced by calcipotriol plus 5-FU treatment (29) and provides evidence that CD4 + T cells infiltrating the actinic keratoses can directly target these malignant keratinocytes. Notably, NKG2D ligand induction on keratinocytes by calcipotriol plus 5-FU treatment has been shown to synergize with TSLP to suppress skin cancer development (3, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Since HPV infection is restricted to the epithelium, with no reliable or effective host immune response, clearance must be mediated by local immune defenses [11]. Cell Mediated Immunity may play a key role at the cellular level for many reason: (a) the squamous epithelium is rich in keratinocytes which can act as non-professional antigen presenting cells (APCs) capable of secreting pro-inflammatory cytokines and chemokines and can induce the activation of CD4 and CD8+ memory T cells into a functional cytokine-secreting and cytotoxic state; [12] (b) there is a preponderance of T lymphocytes, NKT, NK and some B cells at the epidermal-stromal junction beneath the basement membrane of the human cervix; [13] (c) The normal vaginal lavage has also been found to consist predominantly of granulocytes including neutrophils, macrophages, T and B cells [14] which are innate and adaptive effectors; (d) low-grade and high-grade squamous intraepithelial lesions which have persisted or progressed have been shown to have increased numbers of macrophages, neutrophils and lymphocytes in the superficial epithelium compared to the stroma in contrast with uninfected skin or infection with non-carcinogenic types. [11,15] In the cervix, Langerhans cells are specialized epithelial dendritic cells that function in the uptake of antigens.…”
Section: Biology and Immunology Of Hpvmentioning
confidence: 99%
“…Therefore, KC can engage in "nonprofessional" antigen presentation, which may be tolerogenic because of the lack of costimulation. However, KC can express MHC-II in response to IFN-␥, and increased adhesion mediated by intercellular adhesion molecule 1 (ICAM-1) may substitute for CD28 costimulatory interactions (81,82). Using CD28-deficient mice, it was shown that ICAM-1 can provide necessary costimulation for anti-CD3 antibody-mediated T cell proliferation and IL-2 secretion (81).…”
Section: Kc Communicate With Professional Immune Cellsmentioning
confidence: 99%
“…IFN-␥ treatment of immortalized human KC increases the surface expression of ICAM-1 and MHC-II. These cells are then able to process protein antigen and prime antigen-specific memory T cells in an ICAM-1/lymphocyte function-associated antigen 1 (LFA-1)-dependent manner, suggesting that ICAM-1 on KC is able to costimulate MHC-II responses (82). Salient features of KC activation responses are summarized in Fig.…”
Section: Kc Communicate With Professional Immune Cellsmentioning
confidence: 99%